Sacred as secular : secularization under theocracy in Iran - Kazemipur, Abdolmohammad (Advancing studies in religion ;, 2022)
"Debates about Islam and Muslim societies have intensified in the last four decades, triggered by the 1979 Islamic Revolution in Iran and, later, by the events of 9/11. Too often present in these debates are wrongheaded assumptions about the attachment of Muslims to their religion and the impossibility of secularism in the Muslim world. At the heart of these assumptions is the notion of Muslim exceptionalism: the idea that Muslims think, believe, and behave in ways that are fundamentally different from other faith communities. In Sacred as Secular Abdolmohammad Kazemipur attempts to debunk this flawed notion of Muslim exceptionalism by looking at religious trends in Iran since 1979. Drawing on a wide range of data and sources, including national social attitudes surveys collected since the 1970s, he examines developments in the spheres of politics and governance, schools and seminaries, contemporary philosophy, and the self-expressed beliefs and behaviours of Iranian men, women, and youth. He reveals that beneath Iran's religious façade is a deep secularization that manifests not only in individual beliefs, but also in Iranian political philosophy, institutional and clerical structures, and intellectual life. Empirically and theoretically rich, Sacred as Secular looks at the place of religion in Iranian society from a sociological perspective, expanding the debate on secularism from a predominantly West-centric domain to the Muslim world."--